Usus Al-Syari’ah Fi Al-Muamalah: Tabadul Al-Manafi Didalam Produksi - Nuranisyah, Siti; Hasanuddin, Muhammad; Hakim, Atang Abd. (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This study aims to analyze the application of the principle of tabadul al-manafi in production within the framework of Islamic muamalah. The research was conducted using a qualitative approach with a literature review method, focusing on primary sources such as fiqh muamalah texts and secondary sources from recent academic journals. The results indicate that the implementation of tabadul al-manafi in production creates a more just, sustainable, and mutually beneficial economic system. This principle ensures that all parties involved in production receive proportional benefits, without exploitation or harm to any party. The findings support the hypothesis that tabadul al-manafi enhances distributive justice, efficiency, and social harmony in production processes. In conclusion, the principle of tabadul al-manafi is fundamental for building a fair and sustainable economic system in accordance with Islamic values. Further research is recommended to develop practical models for implementing this principle in various industries and to empirically evaluate its impact on corporate performance and social welfare.